Seasonality of soil water exchange in the soybean growing season in southern Brazil (Scientia Agricola, 2015)
The processes of water transfer in the soil-plant-atmosphere system are strongly affected by soil use and management. Differences in the dynamics of soil water transfer between no-tillage (NT) and conventional tillage (CT) practices during a soybean (Glycine max) growing season in southern Brazil were assessed in this study. All the water balance components were analyzed during the soybean growing season (2009/2010). Rainfall, runoff, soil water storage and hydro-physical soil properties were analyzed under two tillage systems. The land-atmosphere water vapor exchanges, obtained from eddy covariance stations, were analyzed with regard to the soybean agroecosystem. Characterizations of soil water storage were also formulated in the 2006/2007 and 2008/2009 soybean growing seasons under the NT system. During the periods without rain, the soil water content under NT was greater than under CT. The soil superficial layer, more porous under NT, contributed to less runoff during rainy events. Moreover, under NT conditions the water supply was always high, between 0.2 - 0.5 m. The total evapotranspiration in the soybean agroecosystem growing season was 410.8 mm.